Method for photocatalytic reduction of CO2 using microporous crystalline metal sulfide photocatalysts

Microcrystalline metal sulfide photocatalysts with a lower band gap width address the inefficiency of existing carbon dioxide conversion methods by enabling effective photocatalytic reduction into valuable carbon-based molecules using visible light, outperforming conventional technologies in productivity.

JP7624417B2Active Publication Date: 2025-01-30IFP ENERGIES NOUVELLES
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021577374
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-06-28
Filing Date
2020-06-16
Publication Date
2025-01-30
Estimated Expiration
2040-06-16

AI Technical Summary

Technical Problem

Existing photocatalytic methods for converting carbon dioxide into valuable carbon-based molecules are limited by high band gap widths in microcrystalline semiconductors, which restrict the absorption of photons from the visible part of the solar spectrum, leading to inefficient photocatalytic performance.

Method used

Employing microcrystalline metal sulfide-based photocatalysts with a lower band gap width, activated by visible light, to facilitate efficient photocatalytic reduction of carbon dioxide into carbon-based molecules by contacting carbon dioxide and a sacrificial compound with the photocatalyst under specific conditions.

Benefits of technology

The method enhances the photocatalytic performance by allowing the absorption of a larger amount of photons, resulting in improved production of carbon-based molecules such as methane, ethanol, and formic acid, surpassing conventional technologies in efficiency and productivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007624417000001
    Figure 0007624417000001
  • Figure 0007624417000002
    Figure 0007624417000002
  • Figure 0007624417000003
    Figure 0007624417000003
Patent Text Reader

Abstract

The present invention relates to a method for the photocatalytic reduction of carbon dioxide carried out in the liquid and / or gas phase under irradiation using a microporous crystalline metal sulfide photocatalyst by contacting a feedstock containing CO and at least one sacrificial compound with the photocatalyst and then irradiating the photocatalyst with at least one irradiation source producing at least one wavelength below the bandgap of the photocatalyst to reduce CO and oxidize the sacrificial compound, producing an effluent at least partially containing C1 or higher carbon molecules other than CO.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The field of the invention is that of the photocatalytic reduction of carbon dioxide (CO2) under light irradiation by the use of photocatalysts. [Background technology]

[0002] Fossil fuels, such as coal, oil and natural gas, are the main traditional energy sources in the world due to their availability, stability and high energy density. However, combustion results in the emission of carbon dioxide, which is considered to be the main cause of global warming. Therefore, there is an increasing need to reduce the emission of CO2 by either capturing the CO2 or converting it.

[0003] Although "passive" carbon capture and sequestration (CCS) is generally considered to be an effective method for reducing CO2 emissions, other strategies need to be envisaged, in particular "active" strategies for converting CO2 into products that have economic value, such as fuels and industrial chemicals.

[0004] Such "active" strategies are based on the reduction of carbon dioxide to give upgradeable products. Carbon dioxide reduction can be performed biologically, thermally, electrochemically or photocatalytically. Among these options, the photocatalytic reduction of CO2 is attracting increasing attention because it can potentially consume alternative forms of energy, for example by powering solar energy, which is abundant, cheap and environmentally clean and safe.

[0005] Photocatalytic reduction of carbon dioxide makes it possible to obtain carbon-based molecules of C1 and above, such as carbon monoxide (CO), methane, methanol, ethanol, formaldehyde, formic acid, or other molecules, such as carboxylic acids, aldehydes, ketones, or various alcohols. These molecules can be converted into directly useful forms of energy, such as methanol, ethanol, formic acid, or methane and all C1 + It can be made into hydrocarbons. Carbon monoxide (CO) can also be upgraded in terms of energy as a mixture with molecular hydrogen for the formation of fuels by Fischer-Tropsch synthesis. The molecules of carboxylic acids, aldehydes, ketones or various alcohols can, for their part, find application in chemical or petrochemical processes. All these molecules are therefore of great interest from an industrial point of view.

[0006] Photocatalysis is based on the principle of activation of one or a set of semiconductors, e.g. photocatalysts, with the energy provided by light irradiation. Photocatalysis can be defined as the absorption of a photon, the energy of which is greater than the band gap width between the valence band and the conduction band, which induces the formation of an electron-hole pair in the case of a semiconductor. Hence, there is the excitation of an electron to the conduction band and the formation of a hole on the valence band. This electron-hole pair will allow the formation of a free radical, which will react with a compound present in the medium, starting an oxidation / reduction reaction, or will recombine according to various mechanisms. A semiconductor is characterized by its band gap, i.e. the energy difference between its conduction band and its valence band, which is inherent to it. Any photon with an energy greater than its band gap can be absorbed by the semiconductor. A photon with an energy lower than its band gap cannot be absorbed by the semiconductor.

[0007] Methods for the photocatalytic reduction of carbon dioxide in the presence of sacrificial compounds are known in the art.

[0008] evaluated the performance qualities of three semiconductors (TiO2, SrTiO3 and CaTiO3) for the photocatalytic reduction of CO2 in aqueous media (Non-Patent Document 1). They observed the production of formaldehyde, formic acid and methanol.

[0009] Anpo et al. investigated the photocatalytic reduction of CO2 with water vapor over TiO2-based photocatalysts immobilized in zeolite micropores (Non-Patent Document 2). These exhibited very high selectivity towards gaseous methanol.

[0010] Mori et al. demonstrated an improvement in the photocatalytic activity of titanium oxide-based microporous or mesoporous crystalline materials compared to bulk titanium dioxide for the reduction of CO2 (Non-Patent Document 3).

[0011] Therefore, while the use of microporous crystalline photocatalysts is known from the state of the art, said photocatalysts often exhibit a high band gap width (>3 eV) and therefore make it possible to upgrade only a minimal part of the photons of the solar spectrum.

[0012] It is known from the prior art to employ non-microporous (bulk) metal sulfide type materials as photocatalysts (Non-Patent Document 4). Materials of this type have the advantage of exhibiting a smaller band gap width (<3 eV) than most metal oxides, e.g. TiO2. [Prior art documents] [Non-patent literature]

[0013] [Non-Patent Document 1] Halmann et al., Solar Energy, 1983, Vol. 31, No. 4, p. 429-431 [Non-Patent Document 2] Anpo et al., "J. Phys. Chem. B", 1997, No. 101, pp. 2632-2636 [Non-Patent Document 3] Mori et al., “RSC Adv.”, 2012, Volume 2, No. 8, p.3165-3172 [Non-Patent Document 4] O. Stroyuk et al., "Chem. Soc. Rev.", Volume 2108, No. 47, p. 5354 Summary of the Invention [Means for solving the problem]

[0014] (Subject of the invention) The object of the present invention is to provide a new, durable and more efficient route for the production of upgradeable carbon-based molecules by photocatalytic conversion of carbon dioxide employing photocatalysts based on microporous crystalline metal sulfides. The method for photocatalytic reduction of CO2 according to the present invention makes it possible to achieve improved performance qualities in comparison with known implementations of this reaction. The prior art photocatalytic reduction method differs from the present invention in that microporous crystalline semiconductors exhibit high band gap widths (>3 eV), which do not allow this material to absorb large amounts of photons originating from the visible part of the solar spectrum. This is because the prior art photocatalytic reduction method uses photocatalysts based on metal sulfides that do not exhibit microporosity. Without being bound to any theory, it is believed that the presence of microporosity in the photocatalyst allows the active charge, electron e - and hole h + This allows for shorter transit times for the ions, thus reducing the recombination rate.

[0015] More particularly, the present invention relates to a method for the photocatalytic reduction of carbon dioxide carried out in the liquid and / or gas phase, comprising the following steps: a) contacting a charge containing carbon dioxide and at least one sacrificial compound with a photocatalyst comprising at least one semiconductor based on a microporous crystalline metal sulfide; b) irradiating the photocatalyst with at least one light source that produces at least one wavelength lower than the band gap width of the photocatalyst, the step being carried out at a temperature of -10°C to 200°C and a pressure of 0.01 MPa to 70 MPa. A method is described, including:

[0016] Advantageously, said photocatalyst comprising at least one semiconductor has the following general formula, in anhydrous terms and in terms of molar terms: X a Y b S8:cR During the ceremony: X represents at least one tetravalent element selected from Sn, Ge, Ti, or Zr; Y represents at least one divalent metal selected from Zn, Cd, and Ni; R represents at least one nitrogenous entity; S is sulfur, "a" is the molar amount of X from 0.1 to 5; "b" is the molar amount of Y of 0.2 to 8; "c" is the molar amount of nitrogenous organism R, 0-4 The compound is provided in a solid form having a chemical composition represented by:

[0017] Advantageously, said photocatalyst comprising at least one semiconductor has, on an anhydrous basis, expressed in terms of moles and having the following general formula: Sn a Zinc b S8:cR During the ceremony: R represents at least one nitrogenous organism; S is sulfur; "a" is the molar amount of Sn of 0.1 to 5; "b" is the molar amount of Zn of 0.2 to 8; "c" is the molar amount of nitrogenous organism R, 0-4 The compound is provided in a solid form having a chemical composition defined by:

[0018] Advantageously, "c" is between 0.2 and 4.

[0019] Advantageously, said solid exhibits an X-ray diffraction diagram which includes at least the lines listed in Table 1 below.

[0020] [Table 1] In the table: VS=very strong; S=strong; m=neutral; w=weak.

[0021] Advantageously, R is an organic compound containing at least two nitrogen atoms.

[0022] Advantageously, R is 1,3-bis(4-piperidinyl)propane.

[0023] Advantageously, the semiconductor has a micropore volume of 0.01 to 0.50 cm 3 / g.

[0024] Advantageously, the band gap width of the photocatalyst is between 1.24 and 3 eV.

[0025] In one embodiment according to the invention, when the method is carried out in the gas phase, the sacrificial compound is a gaseous compound selected from water, ammonia, hydrogen, methane and an alcohol.

[0026] In one embodiment according to the invention, when the method is carried out in the liquid phase, the sacrificial compound is a soluble solid or liquid compound selected from water, ammonia, an alcohol, an aldehyde or an amine.

[0027] Advantageously, the light irradiation source is a natural light irradiation source.

[0028] Preferably, the light irradiation source emits in at least one wavelength range greater than 280 nm.

[0029] More preferentially, the light irradiation source emits in at least one wavelength range between 315 nm and 800 nm. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] (Definitions and Abbreviations) The term "sacrificial compound" corresponds to a compound, in gaseous or liquid form, that can be oxidized.

[0031] Term “C1 or higher (C 1+ "Carbon-based molecules of" are understood to mean molecules resulting from the reduction of CO2 containing one or more carbon atoms, excluding CO2. Such molecules are, for example, CO, methane, methanol, ethanol, formaldehyde, formic acid, methane or other molecules, such as carboxylic acids, aldehydes, ketones, various alcohols or hydrocarbons, containing more than two carbon atoms.

[0032] The groups of chemical elements correspond to the groups of the CAS classification (CRC Handbook of Chemistry and Physics, published by CRC Press, edited by DR Lide, 81st ed., 2000-2001). For example, group VIII according to the CAS classification corresponds to the metals in columns 8, 9 and 10 according to the new IUPAC classification.

[0033] The textural and structural properties of the supports and catalysts described below are determined by characterization methods known to those skilled in the art.

[0034] Micropore volume and pore distribution are determined by nitrogen porosimetry as described in the monograph "Adsorption by Powders and Porous Solids. Principles, Methodology and Applications" by F. Rouquerol, J. Rouquerol and K. Sing (Academic Press, 1999).

[0035] The term "specific surface" refers to the BET specific surface area (SBET :m 2 / g), which is determined by nitrogen adsorption according to standard ASTM D 3663-78, derived from the Brunauer-Emmett-Teller method described in the periodical The Journal of the American Chemical Society, 1938, 60, 309.

[0036] The maximum wavelength that can be absorbed by a semiconductor is calculated using the following formula:

[0037]

number

[0038] Here, λ max is the maximum wavelength (m) that can be absorbed by the semiconductor, and h is the Planck constant (4.13433559×10 -15 eV s), and c is the speed of light in a vacuum (299792458 m s -1 ), and E g is the band gap width of the semiconductor (eV).

[0039] The term "reaction medium" is understood to mean the mixture formed by the charge containing carbon dioxide, the sacrificial compound and the photocatalyst.

[0040] In the present specification, according to the IUPAC convention, the term "micropores" is understood to mean pores whose diameter is less than 2 nm, i.e. less than 0.002 μm; "mesopores" is understood to mean pores whose diameter is 2 nm or more, i.e. 0.002 μm or more and less than 50 nm, i.e. less than 0.05 μm, and "macropores" is understood to mean pores whose diameter is 50 nm or more, i.e. 0.05 μm or more.

[0041] Detailed Description of the Invention The present invention relates to a method for the photocatalytic reduction of carbon dioxide carried out in the liquid and / or gas phase, comprising the following steps: a) contacting a charge containing carbon dioxide and at least one sacrificial compound with a photocatalyst comprising at least one semiconductor based on a microporous crystalline metal sulfide; b) irradiating the photocatalyst with at least one light source that produces at least one wavelength lower than the band gap width of the photocatalyst, and performing step b) at a temperature between -10°C and 200°C and a pressure between 0.01 MPa and 70 MPa. The method includes:

[0042] (Step a) of contacting the charge, at least one sacrificial compound and a microporous crystalline metal sulfide-based photocatalyst) According to step a) of the method according to the invention, a charge containing carbon dioxide (CO2) and at least one sacrificial compound is contacted with a microporous crystalline metal sulfide-based photocatalyst.

[0043] The contacting operation can be carried out by any means known to those skilled in the art. The contacting of the charge and the photocatalyst can be carried out in a closed fixed bed, a sweeping fixed bed or in a suspension (also called a "slurry"). The photocatalyst can also be deposited directly on the optical fiber.

[0044] When the contact treatment is in a closed fixed bed, the photocatalyst is preferentially deposited as a layer on a porous support, for example of the ceramic or metallic sintered type, and the charge containing the carbon dioxide to be converted in gaseous and / or liquid form is passed through the photocatalyst bed.

[0045] When the contact treatment is in a sweep-through fixed bed, the photocatalyst is preferentially deposited on a non-porous support, of ceramic or metallic type, and the load containing the carbon dioxide to be converted in gaseous and / or liquid form is passed over the photocatalyst bed.

[0046] When the contact treatment is in suspension, the photocatalyst is preferentially in the form of particles in suspension in a liquid or liquid / gas charge containing carbon dioxide. In suspension, the process can be carried out in a closed reactor or continuously.

[0047] (Charge and Sacrificial Compounds) The process is carried out in gas or liquid phase or in two phases, gas and liquid, meaning that the charge to be treated by the process is provided in gaseous, liquid or two phases, gas and liquid, respectively. Preferably, the process is carried out in the gas phase.

[0048] When the method is carried out in the gas phase and the charge is provided in gaseous form, the CO2 present in the charge is also in gaseous form and the sacrificial compound(s) used for step a) are also in gaseous form.

[0049] The gaseous sacrificial compound is an oxidizable compound, such as water (H2O), ammonia (NH3), molecular hydrogen (H2), methane (CH4) or even an alcohol, or a mixture thereof. Preferably, the gaseous sacrificial compound is water or molecular hydrogen. If the method is carried out in the gas phase, a diluent fluid, such as N2 or Ar, may be present in the reaction medium. The presence of a diluent fluid is not required to carry out the invention; however, it may be useful to add said diluent to the charge to ensure the dispersion of the charge and / or the photocatalyst in the reaction medium, the control of the adsorption of reactants / products at the surface of the photocatalyst, the control of the absorption of photons by the photocatalyst, the dilution of the products to limit recombination of the products and other side reactions of the isotopes. The presence of a diluent fluid also makes it possible to control the temperature of the reaction medium, which therefore compensates for possible endothermic / exothermic reactions of the photocatalytic reaction. The nature of the diluent fluid is chosen so that its effect is neutral on the reaction medium or its possible reactions do not impair the performance of the desired reaction of carbon dioxide.

[0050] When the method is carried out in the liquid phase and the charge is provided in liquid form, the charge can be in ionic, organic or aqueous form. Charges in liquid form are preferentially aqueous.

[0051] If the liquid charge is an aqueous solution, CO2 is dissolved in the form of aqueous CO2, bicarbonate or carbonate. The sacrificial compound used in this case is a liquid or solid oxidizable compound that is soluble in the liquid charge, such as water (H2O), ammonia (NH3), alcohols, aldehydes or amines. Preferably, the sacrificial compound is water. The pH is generally between 2 and 12, preferably between 3 and 10.

[0052] In some cases, a basic or acidic agent may be added to the aqueous liquid charge to adjust the pH of the charge. The basic agent may be selected from alkali metal or alkaline earth metal hydroxides or organic bases, such as amines or ammonia. The acidic agent may be selected from inorganic acids, such as nitric acid, sulfuric acid, phosphoric acid, hydrochloric acid or hydrobromic acid, or organic acids, such as carboxylic acids or sulfonic acids.

[0053] In some cases, when the liquid load is aqueous, the liquid load may contain any amount of any solvated ions, e.g., K + , Li + , Na + , Ca 2+ , Mg 2+ , SO4 2- , Cl - , F - or NO3 2- It may contain:

[0054] (Photocatalyst) The photocatalyst comprises, and preferably consists of, one or more semiconductors based on microporous crystalline metal sulfides.

[0055] Preferably, the semiconductor has the following general formula, on an anhydrous basis and in terms of molar amounts: X a Y bS8:cR During the ceremony: X represents at least one tetravalent element selected from Sn, Ge, Ti, or Zr; Y represents at least one divalent metal selected from Zn, Cd, and Ni; R represents at least one nitrogenous organism; S is sulfur, "a" is the molar amount of X from 0.1 to 5; "b" is the molar amount of Y of 0.2 to 8; "c" is the molar amount of nitrogenous organism R, 0-4 The compound is provided in a solid form having a chemical composition represented by

[0056] More preferentially, said photocatalyst comprises a solid called IZM-5, said solid IZM-5 being expressed in terms of moles, on an anhydrous basis, and having the following general formula: Sn a Zinc b S8:cR During the ceremony: R represents at least one nitrogenous organism; S is sulfur; "a" is the molar amount of Sn of 0.1 to 5, preferably 1 to 4; "b" is the molar amount of Zn of 0.2 to 8, preferably 0.2 to 2; "c" is the molar amount of nitrogenous organic matter R of 0 to 4, preferably 0.5 to 3. It has a chemical composition defined by:

[0057] Preferably, R contains two nitrogen atoms and, very preferentially, R is 1,3-bis(4-piperidinyl)propane, the expanded formula of which is given below:

[0058] [ka]

[0059] The component semiconductors of the photocatalyst are crystalline and exhibit very specific X-ray diffraction signals. More preferentially, the photocatalyst comprises solid IZM-5 and exhibits an X-ray diffraction pattern that includes at least the lines listed in Table 1 above.

[0060] Relative Intensity I rel is given for a relative intensity scale in which a value of 100 is assigned to the most intense line in the X-ray diffractogram: 5≦w<10; 10≦m<15; 15≦S<50; VS≧50.

[0061] The diffraction pattern is obtained by radiation crystallographic analysis on a diffractometer using conventional powder techniques with copper Kα1 radiation (λ=1.5406 Å). Based on the positions of the diffraction peaks, expressed by the angle 2θ, the interlattice spacings d characteristic of the sample are hkl is calculated using Bragg's law. d hkl The measurement error Δ(d hkl ) is calculated as a function of the absolute error Δ(2θ) assigned to the measurement of 2θ by Bragg's law. An absolute error Δ(2θ) equal to ±0.02° is generally accepted. hkl The relative intensity I assigned to each value of rel is measured according to the height of the corresponding diffraction peak. hkl In the value column, the average lattice spacing is given in angstroms (Å). Each of these values ​​has a measurement error Δ(d hkl ) must be assigned to

[0062] The micropore volume of the component semiconductor of the photocatalyst is preferably 0.01 to 0.50 cm 3 / g, preferably 0.05 to 0.30 cm 3 / g.

[0063] The band gap width of the photocatalyst is preferably 1.24 to 3 eV.

[0064] The photocatalyst may optionally be doped with one or more ions selected from metal ions, e.g., ions of V, Ni, Cr, Mo, Fe, Sn, Mn, Co, Re, Nb, Sb, La, Ce, Ta or Ti, non-metal ions, e.g., ions of C, N, S, F or P, or a mixture of metal and non-metal ions.

[0065] The photocatalyst may optionally contain particles containing one or more elements in metallic state selected from elements from groups IVb, Vb, VIB, VIIb, VIIIb, Ib, IIb, IIIa, IVa and Va of the Periodic Table of Elements. The particles containing one or more elements in metallic state are in direct contact with the semiconductor. The particles may consist of a single element in metallic state or of several elements in metallic state capable of forming an alloy. The term "element in the metal state" is understood to mean an element belonging to the family of metals (not to be mixed with "metal element"), the element being in zero oxidation state (and therefore in metallic form). Preferably, the element(s) in metallic state are selected from metallic elements from groups VIIb, VIIIb, Ib and IIb of the Periodic Table of the Elements, particularly preferably from platinum, palladium, gold, nickel, cobalt, ruthenium, silver, copper, rhenium or rhodium. The particles containing one or more elements in metallic state are preferentially provided in the form of particles having a size between 0.5 nm and 1000 nm, preferably between 0.5 nm and 100 nm, even more preferentially between 1 and 20 nm.

[0066] The photocatalyst used in the method according to the invention can be provided in different forms or shapes (nanometric powders, nanoobjects containing or not containing cavities, thin films, monoliths, beads of micrometer or millimeter size, etc.) The photocatalyst is advantageously provided in the form of a nanometric powder.

[0067] (Method for preparation of photocatalyst) The component semiconductors of the photocatalyst can be obtained by the preparation methods described below. i) mixing at least one source of a tetravalent element, denoted X, at least one source of a divalent metal, denoted Y, at least one source of sulfur, denoted S, at least one organic substance, denoted R, and optionally at least one solvent, denoted SOLV, comprising at least one aqueous compound (denoted A) and / or at least one organic compound (denoted O), to obtain a precursor gel; said mixture preferentially exhibits the following molar composition: X / Y: at least 0.1, preferably 1 to 200; S / (X+Y): 0.05 to 50, preferably 0.1 to 20, R / (X+Y): 0.05 to 50, preferably 0.1 to 20, SOLV / (X+Y): 0 to 200, preferably 1 to 100, A / O: 0.005 to 100, preferably 0.1 to 20, ii) heat treatment of said precursor gel obtained at the end of step i) at a temperature between 120° C. and 250° C. for a time period between 2 and 21 days.

[0068] The preparation method consists in preparing a reaction mixture, called gel, containing at least one source of a tetravalent element, denoted X, at least one source of a divalent metal, denoted Y, at least one source of sulfur, denoted S, at least one organic substance R, and optionally a solvent. The amounts of said reactants are adjusted to give on this gel a composition allowing its crystallization, and which has the general formula X a Y b A crystalline solid of S8:cR (where a, b and c meet the criteria defined above) is provided in its crude synthetic form.

[0069] (Step i) The mixing step i) is carried out for a period of preferably 15 minutes or more, preferably with stirring at low or high shear rates by any system known to those skilled in the art, until a homogeneous mixture is obtained. At the end of step i), a homogeneous precursor gel is obtained.

[0070] It may be advantageous to add seeds to the reaction mixture during said step i) of the method according to the invention in order to shorten the time required for the formation of crystals and / or the total duration of crystallization. Said seeds also suppress impurities and promote the formation of crystalline solids. Such seeds include crystalline solids, in particular solid crystals. The crystalline seeds are generally added in a proportion of 0.01% to 10% by weight, relative to the total weight of the tin and zinc precursors used in the reaction mixture.

[0071] It may be advantageous to carry out an ageing of the reaction mixture during said step i) of the process according to the invention prior to the heat treatment in order to control the size of the crystals of the crystalline solid. Said ageing also promotes the formation of said crystalline solid, suppressing impurities. Ageing of the reaction mixture during said step i) of the process according to the invention may be carried out at ambient temperature or at a temperature between 20 and 100° C., with or without stirring, advantageously for a period between 30 min and 48 h.

[0072] In the case where the photocatalyst comprises solid IZM-5, said solid IZM-5 is obtained by reacting a mixture comprising at least one source of tin, denoted Sn, at least one source of zinc, denoted Zn, at least one source of sulfur, denoted S, at least one nitrogenous organic substance, denoted R, and optionally at least one solvent, denoted SOLV, comprising at least one aqueous compound (denoted A) and / or at least one organic compound (denoted O), this mixture preferentially exhibiting the following molar composition: Sn / Zn: at least 0.1, preferably at least 1, more preferably 2 to 200; S / (Sn+Zn): 0.1 to 20, preferably 1 to 10, R / (Sn+Zn): 0.1 to 10, preferably 1 to 5, SOLV / (Sn+Zn): 0 to 200, preferably 10 to 100, more preferably 20 to 100, A / O: 0.01 to 10, preferably 0.1 to 8, and preferably 0.2 to 5.

[0073] R is a nitrogenous organic compound having at least one nitrogen atom; preferably R contains two nitrogen atoms and acts as an organic structuring. Preferably R is the nitrogenous compound 1,3-bis(4-piperidinyl)propane. The nitrogenous organic compound used as a structuring agent for the crystalline solid IZM-5 is synthesized by any method known to those skilled in the art.

[0074] The source of tin employed to carry out the process for the preparation of the crystalline solid IZM-5 can be any compound that contains tin element and is capable of releasing this element in active form to the mixture. The source of tin is preferably tin acetate Sn(CH3CO2)4, tin tert-butoxide Sn(OC(CH3)3)4, tin tetrachloride SnCl4, tin bis(acetylacetonate) dichloride (CH3COCH=C-(O-)CH3)2SnCl2, tin oxide SnO2 or tin Sn in metallic form.

[0075] The source of zinc employed to carry out the process for the preparation of the crystalline solid IZM-5 can be any compound that contains elemental zinc and is capable of releasing this element in an active form into the mixture. The source of zinc is preferably zinc chloride ZnCl2, zinc acetate Zn(CH3CO2)2, zinc sulfate ZnSO4, zinc nitrate Zn(NO3)2, zinc oxide ZnO or zinc Zn in metallic form.

[0076] The source of sulfur employed to carry out the process for the preparation of crystalline solid IZM-5 can be any compound that contains elemental sulfur and is capable of releasing this element in active form into the mixture. The source of sulfur is preferably solid or liquid under standard conditions of temperature and pressure. The source of sulfur is preferably elemental sulfur S or S8, sodium sulfide Na2S, potassium sulfide K2S, lithium sulfide Li2S, ammonium sulfide (NH4)2S or dimethyl disulfide CH3SSCH3.

[0077] The solvent employed for the implementation of the process for the preparation of the crystalline solid IZM-5 can be an aqueous and / or organic compound. According to one alternative form, the solvent consists of an aqueous compound and an organic compound. The aqueous compound is preferably selected from water H2O, and the organic compound is preferably selected from compounds of the alcohol (preferably ethanol, isopropanol), diol (preferably ethylene glycol, propylene glycol), triol (preferably glycerol or propane-1,2,3-triol), organosulfur compound (preferably dimethylsulfoxide or DMSO) or organonitrogen compound (preferably dimethylformamide or DMF) type, which are liquid under standard temperature and pressure conditions.

[0078] According to another alternative form, no additional solvent is used in the method for the preparation of crystalline solid IZM-5, which is a nitrogenous organic denoted by R when it is in liquid form under standard conditions of temperature and pressure allowing the dissolution of the metal precursor and the sulfur-based precursor.

[0079] (Step ii) According to step ii) of the preparation process, the gel obtained at the end of step i) is subjected to a heat treatment, preferentially at a temperature between 120° C. and 250° C., for a period between 2 and 21 days, until a crystalline solid is formed.

[0080] The gel is advantageously placed under autogenous reaction pressure, optionally with the addition of a gas, such as nitrogen, at a temperature between 120° C. and 250° C., preferably between 140° C. and 210° C., until solid crystals are formed in their crude synthetic form.

[0081] The time required to obtain crystallization generally varies between one day and several months depending on the composition of the reactants in the gel, the stirring and the reaction temperature. Preferably, the crystallization time varies between 2 and 21 days, preferably between 5 and 15 days.

[0082] The reaction is generally carried out with or without stirring, preferably with stirring. As stirring system, any system known to those skilled in the art may be used, for example, pitched blades with baffles, stirred turbomixers or Archimedes screws.

[0083] Upon completion of the heat treatment step, which results in the crystallization of the solid, the solid phase is preferably filtered off, washed and then dried. Preferably, the washing step will be carried out with ethanol or the solvent used for the synthesis.

[0084] Advantageously, at the end of the heat treatment step ii), and optionally at the end of the abovementioned filtering, washing and drying steps, a step of extraction of the organism R is carried out by any method known to the skilled artisan to liberate the microporosity. Preferably, this step can be carried out by means of a heat treatment at 100° C. to 1000° C. under air, oxygen, hydrogen, H2S or under an inert gas, for example N2, either alone or in a mixture. This extraction is carried out by means of an extraction agent, for example NH4 + , alkali metals, alkaline earth metals or any metal cation.

[0085] (Photocatalyst irradiation step b)) According to step b) of the method according to the invention, the photocatalyst is irradiated by at least one radiation source producing at least one wavelength absorbable by the catalyst (i.e. lower than the band gap width of the constituent semiconductors of said photocatalyst, in the alternative form in which the photocatalyst consists of at least one semiconductor), and carbon dioxide is reduced and the sacrificial compound is oxidized in the presence of said photocatalyst activated by said radiation source, producing an effluent containing, at least in part, carbon-based molecules of C1 or higher other than CO2.

[0086] Photocatalysts including one or more microporous crystalline metal sulfide based semiconductors can be activated by the absorption of at least one photon.

[0087] An absorbable photon is one whose energy is greater than the band gap width. In other words, the photocatalyst can be activated by at least one photon having a wavelength that corresponds to or is lower than the energy associated with the band gap width of the semiconductor that constitutes the photocatalyst.

[0088] Any light irradiation source suitable for activating the photocatalyst, i.e. emitting at least one wavelength that can be absorbed by the photocatalyst, can be used according to the invention. The light irradiation source can be artificial, of the type of laser, Hg, incandescent lamp, fluorescent tube, plasma or light-emitting diode (LED), just as it can be natural, by solar irradiation. Advantageously, the light irradiation source is natural, preferably by solar irradiation.

[0089] The light irradiation source produces radiation, at least a portion of whose wavelengths is at the maximum wavelength (λ ) that can be absorbed by the component semiconductor of the photocatalyst according to the invention. max) When the photoirradiation source is solar radiation, it generally emits in the ultraviolet, visible and infrared spectrum, i.e. it emits in the wavelength range of approximately 280 nm to 2500 nm (according to standard ASTM G173-03). Preferably, this source emits in at least one wavelength range greater than 280 nm, highly preferably between 315 nm and 800 nm, which includes the UV spectrum and / or the visible spectrum.

[0090] The light irradiation source provides a stream of photons that irradiate the reaction medium containing the photocatalyst. The interface between the reaction medium and the light source varies depending on the application and the nature of the light source.

[0091] When the light irradiation source is natural, e.g. solar irradiation, the light irradiation source is located outside the reactor and the interface between the two can be an optical window made from Pyrex, quartz or organic glass or any other interface that allows photons that can be absorbed by the photocatalyst according to the invention to diffuse from the external environment into the reactor.

[0092] The implementation of the photocatalytic reduction of carbon dioxide can be conditioned by the supply of suitable photons to the photocatalytic system for the envisaged reaction and for the reason that it is not limited to a specific pressure or temperature range apart from that which makes it possible to ensure the stability of the product(s). The temperature range employed for the photocatalytic reduction of the carbon dioxide-containing charge is generally from -10°C to +200°C, preferably from 0 to 150°C, highly preferably from 0 to 50°C. The pressure range employed for the photocatalytic reduction of the carbon dioxide-containing charge is generally from 0.01 MPa to 70 MPa (0.1 to 700 bar), preferably from 0.1 MPa to 5 MPa (1 to 50 bar).

[0093] Dilution fluids, such as those described in step a), may be present in the reaction medium if the method is carried out during irradiation in the gas phase.

[0094] The effluent obtained after the reaction for the photocatalytic reduction of carbon dioxide contains, on the one hand, at least one C or higher molecule other than carbon dioxide resulting from the reaction, and, on the other hand, unreacted charge, and also optionally dilution fluids, but also parallel reaction products resulting from the photocatalytic reduction of HO, if this compound is used as sacrificial compound, such as molecular hydrogen.

[0095] The following examples illustrate the present invention but do not limit the scope of the invention.

[0096] (Example) (Example 1: Photocatalyst A-TiO2) Photocatalyst A is a semiconductor based on commercially available TiO2 (Aeroxide® P25, Aldrich®, purity >99.5%). The particle size of the photocatalyst is 21 nm as measured by transmission electron microscopy (TEM), and the specific surface area is 52 m2 as measured by the BET method. 2 / g.

[0097] Photocatalyst A has a band gap width of 3.1 eV as measured by UV-visible diffuse reflectance spectrometry, and does not exhibit microporosity.

[0098] Example 2: Preparation of solid IZM-5 0.228 g of tin dioxide (SnO2, 99% purity by weight, Sigma-Aldrich) was mixed with 0.146 g of zinc nitrate (Zn(NO3)2·6H2O, 99% purity by weight, Alfa Aesar). Then, 0.277 g of sulfur (S, 99.98% purity by weight, Aldrich) and 2.001 g of 1,3-bis(4-piperidyl)propane (compound R, 97% purity by weight, Aldrich) were added to the previous mixture. Finally, 11.2 mL of ethylene glycol (99.8% purity by weight, VWR) and 3.7 mL of deionized water were incorporated and stirring (250 rpm) of the synthesis gel was maintained for 30 min. The precursor gel was then transferred to an autoclave after homogenization. The autoclave was closed and then heated at 190 °C under static conditions for 12 days. The resulting crystalline product is filtered, washed with ethanol, and then dried at 100° C. overnight. The crude solid synthesis product is analyzed by X-ray diffraction and confirmed to consist of solid IZM-5. The product exhibits a Sn / Zn molar ratio of 5.7, as determined by ICP-MS. Elemental analysis gives the following molar composition: Sn 3.4 Zinc 0.6 S8:1.1R.

[0099] (Example 3: Photocatalyst B) The solid obtained in Example 2 is subjected to a heat treatment to extract all or part of the compound R and to release the microporosity. A mixture containing 50% by volume of N2 and 50% by volume of air is introduced at a flow rate of 2 SL / h / g into a closed-bed type reactor containing the solid IZM-5 obtained in Example 2. The temperature is increased to 120°C at a rate of 1°C / min and then left for 1 hour. In a second step, the temperature is increased to 300°C at a rate of 1°C / min and then left for 2 hours. Finally, the temperature is reduced again to ambient temperature by the inertia of the reactor.

[0100] The recovered solid is called catalyst B. Photocatalyst B has a band gap width of 2.6 eV as measured by UV-visible diffuse reflectance spectroscopy, and a micropore volume of 0.1 mL / g.

[0101] (Example 4: Use of photocatalysts A and B in the photocatalytic reduction of CO2 in the gas phase) Solids A and B are subjected to a test of the photocatalytic reduction of CO in the gas phase in a continuous closed bed reactor. The reactor is made of steel and equipped with an optical window with a specific surface area of ​​5.3×10 -4 m 2 and has sintered glass facing an optical window on which a photocatalytic solid is deposited.

[0102] Approximately 100 mg of photocatalyst is deposited on the sintered glass. The test is carried out at ambient temperature and atmospheric pressure. A flow rate of 18 mL / h of CO2 is passed through a water saturator and then through the reactor. The production of CH4 and CO resulting from the reduction of carbon dioxide is monitored by analysis of the effluent every 6 minutes by micro gas chromatography. The UV-visible light irradiation source is provided by a Xe-Hg lamp (Asahi®, MAX302®). The light irradiation power is measured in the wavelength range 315 nm to 400 nm and is constantly 130 W / m 2 The duration of this test is 20 hours.

[0103] The average photocatalytic activity comparison is expressed in μmol of methane or carbon monoxide produced per hour and per illuminated surface area. The results are given in Table 2 below. The activity values ​​show that the use of the solids according to the invention exhibits the best photocatalytic performance qualities.

[0104] [Table 2]

Claims

1. A method for the photocatalytic reduction of carbon dioxide carried out in the gas phase, comprising the following steps: a) contacting a charge containing carbon dioxide and at least one sacrificial compound with a photocatalyst comprising at least one semiconductor based on a microporous crystalline metal sulfide; said photocatalyst comprising at least one semiconductor is represented on an anhydrous basis in terms of moles and has the following general formula: Sn a Zn b S 8 :cR During the ceremony: R is 1,3-bis(4-piperidinyl)propane; S is sulfur; "a" is the molar amount of Sn of 0.1 to 5; "b" is the molar amount of Zn from 0.2 to 8; "c" is the molar amount of nitrogenous organism R from 0 to 4 providing in a solid form having a chemical composition defined by b) irradiating the photocatalyst with at least one light source producing at least one wavelength lower than the band gap width of the photocatalyst, at a temperature between −10° C. and 200° C. and a pressure between 0.01 MPa and 70 MPa. A method comprising:

2. 2. The method of claim 1, wherein "c" is from 0.2 to 4.

3. 3. The method of claim 2, wherein the solid exhibits an X-ray diffraction pattern that includes at least the lines listed in the table below. 【Table 1】 In the table, VS = very strong; S = strong; m = medium; w = weak

4. The semiconductor has a micropore volume of 0.01 to 0.50 cm 3 The method according to any one of claims 1 to 3, wherein the molecular weight is 1 / g.

5. The method according to any one of claims 1 to 4, wherein the band gap width of the photocatalyst is 1.24 to 3 eV.

6. The method according to claim 1, wherein the sacrificial compound is a gaseous compound selected from water, ammonia, hydrogen, methane and an alcohol.

7. The method of any one of claims 1 to 6, wherein the light irradiation source emits in at least one wavelength range above 280 nm.

8. The method of claim 7, wherein the light irradiation source emits light in at least one wavelength range from 315 nm to 800 nm.

Citation Information

Patent Citations

  • Nano indium sulfide photocatalyst as well as preparation method and application thereof

    CN103962156A

  • Method for photocatalytic reduction of carbon dioxide using supported photocatalysts made from molybdenum sulfide or tungsten sulfide

    JP2021502891A

  • System for Harvesting Oriented Light for Carbon Dioxide Reduction

    US20140251786A1

  • Method for the photocatalytic reduction of carbon dioxide implementing a supported photocatalyst made from molybdenum sulfide or tungsten sulfide

    WO2019096657A1